Collision [compact disc, unabridged] - Abbott, Jeff (Brilliance Audio, 2008)
Two men are thrown together by an unexpected, violent event. While they are vastly different - one is a corporate consultant mourning the murder of his wife, the other is ex CIA, on a very dangerous assignment with a fringe agency - they realize they must work together in order to escape the setup planned for them.